Adoptive Cell Transfer of Allogeneic Epstein–Barr Virus-Specific T Lymphocytes for Treatment of Refractory EBV-Associated Posttransplant Smooth Muscle Tumors: A Case Report - Hansen, Bjoern-Thore; Bacher, Petra; Eiz-Vesper, Britta; Heckl, Steffen M.; Klapper, Wolfram; Koch, Karoline; Maecker-Kolhoff, Britta; Baldus, Claudia D.; Fransecky, Lars (Frontiers in Immunology, 2021)
Posttransplant smooth muscle tumors (PTSMTs) are rare Epstein–Barr virus (EBV)-associated neoplasms, mostly occurring after solid organ transplantation. Current therapeutic strategies include surgery and reduction of immunosuppressive medication. We describe for the first time a novel treatment approach for PTSMT by adoptive cell transfer (ACT) of EBV-specific T cells to a 20-year-old patient with a medical history of cardiac transplantation, posttransplant lymphoproliferative disease, and multilocular PTSMT. During ACT, mild cytokine release syndrome occurred, while no unexpected safety signals were recorded. We observed in vivo expansion of EBV-specific T cells and reduction of EBV viremia. Best response was stable disease after 4 months with reduction of EBV viremia and normalization of lactate dehydrogenase levels. ACT with EBV-specific T cells may be a safe and efficacious therapeutic option for PTSMT that warrants further exploration.